2012
DOI: 10.1080/08927014.2012.662675
|View full text |Cite
|
Sign up to set email alerts
|

The effect of substratum type, orientation and depth on the development of bacterial deep-sea biofilm communities grown on artificial substrata deployed in the Eastern Mediterranean

Abstract: An increasing number of deep-sea studies have highlighted the importance of deep-sea biofouling, especially in relation to the protection of deep-sea instruments. In this study, the microbial communities developed on different substrata (titanium, aluminum, limestone, shale and neutrino telescope glass) exposed for 155 days at different depths (1500 m, 2500 m, 3500 m and 4500 m) and positions (vertical and horizontal) in the Eastern Mediterranean Deep Sea were compared. Replicated biofilm samples were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 79 publications
4
34
1
1
Order By: Relevance
“…So far, only a few studies have been devoted to biofilm development on artificial surfaces in deep-sea environment. Nevertheless, a recent study reported that substrate types and orientation were less important than depth in shaping the microbial composition of deep-sea biofilms at 1,500–4,500 m depth in the eastern Mediterranean Sea9. Our results also support the importance of environments, rather than substrata, in shaping the microbial structures of biofilms.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…So far, only a few studies have been devoted to biofilm development on artificial surfaces in deep-sea environment. Nevertheless, a recent study reported that substrate types and orientation were less important than depth in shaping the microbial composition of deep-sea biofilms at 1,500–4,500 m depth in the eastern Mediterranean Sea9. Our results also support the importance of environments, rather than substrata, in shaping the microbial structures of biofilms.…”
Section: Discussionsupporting
confidence: 83%
“…So far, there has been only one study that reported biofilm formation on artificial substrata in water column from surface water to deep-sea waters9 but there has been no study to reveal formation mechanisms of biofilms in deep-sea extreme environments, such as cold seeps and brine pools. Cold seeps are formed by subsurface fluid expulsions to the seabed, due to differential pressure gradients and tectonic activity at both active and passive continental margins1011.…”
mentioning
confidence: 99%
“…The parameters fluid density (q) and dynamic viscosity (l) of 1024.75 kg m À3 and 1.08 Â 10 À3 Pa s, respectively, correspond to values of seawater at laboratory temperature of 20 C. 31 Velocity boundary condition was imposed at the flow inlet section, while a constant pressure (101 325 Pa) was imposed at the outlet boundary. Finally, no-slip conditions were applied at the solid walls of the modelled device.…”
Section: B Computational Fluid Dynamic (Cfd) Simulationsmentioning
confidence: 99%
“…Bellou et al (2012) found a difference in colonization of microbial communities on substratum types and suggested that substratum type may influence the microbial community. Similarly, microbial communities developed on artificial substrata, i.e., granite and petri dish (Chung et al, 2010), glass slides, ceramic tiles, coral skeletons and reef sediments (Witt et al, 2011) have also been shown to be influenced by substratum type.…”
Section: Introductionmentioning
confidence: 95%